MONUMENTA BRASILIAE - Leite, Serafim (MONUMENTA HISTORICA SOCIETATIS IESU ;, 1956)
CONTENIDO: V.1. 1538-1553 -- V.2. 1553-1558 -- V.3. 1558-1563 -- V.4. 1563-1568 -- V.5. SIVE COMPLEMENTA AZEVEDIANA I1539-1565.